Analysis Of The Influence Of Brand Association, Experiental Marketing And Brand Trust On Consumer Loyalty For National Digital Game Products - Bahtiar Efendi; Zunan Setiawan; Lalang Saksono; Silvia Ekasari; Musran Munizu (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to examine the potential effects of brand association, brand trust, and experiential marketing on consumer loyalty and purchase decisions. Only people who enjoy video games were included in the study's population. With a total of 100 samples, the sample was chosen using a non-probability sampling approach called purposive sampling. In order to collect data for this study, questionnaires were distributed in accordance with the descriptive statistical analysis methodology. The author must create a relationship model between variables referred to in this instance as a path diagram before he can apply path analysis in his research. There is a strong positive correlation between experiential marketing and brand association in purchase decisions, according to the results of the data processing that was done. The fact that the t-count value is greater than the t-table value indicates this. The computed t-value does not exceed the value in the t-table, indicating that there is no significant positive connection with the brand trust variable. The Sig value is smaller than the author's conventional significance criterion of 0.05, indicating that experiential marketing, brand trust, and brand association have a substantial impact on purchasing decisions. According to the partial test, customer loyalty is significantly impacted negatively by the factors experiential marketing, brand trust, and brand association.